Estudos dendrocronológicos e da qualidade da madeira de árvores de Khaya ivorensis A. Chev. - Soranso, Denise Ransolin (2015)
This study aimed to evaluate the potential for dendrochronological studies and the influence of planting spacing on diameter growth and wood quality from Khaya ivorensis trees. To assess the dendrochronological potential of the species, the material came from eighteen-year-old experimental plantations of Vale’s Natural Reserve, situated in the city of Linhares, ES, Brazil. Samples for spacing influence analysis were derived from a five-year-old experimental plantation, belonging to the company Atlântica Agropecuária, located in Pirapora, MG, Brazil. For the dendrochronological study (growth rings), we obtained data relative to tree diameter and collected discs from the base of five trees. The samples were sanded and polished and then we identified the growth rings proceeding with scanning at high resolution and subsequent microscopic study of the wood. To evaluate the influence of planting spacing, radial samples of 10 individuals were obtained, extracted at 0.40 cm above the ground. We determined the apparent density (X-ray densitometry) and performed morphological characterization of the wood fibers. Data were subjected to analysis of variance and means were compared by Tukey’s test. Khaya ivorensis trees presented dendrochronological potential, with the limits of their growth rings marked by a thin marginal parenchyma layer. The radial growth of the wood was uneven in the early years, with differentiation of the average diameter of the vessel elements in the analyzed positions. Regarding the planting spacing, there was greater diameter growth and mean annual increment (MAI) in diameter for the trees planted in spacings of greater amplitude (7x6 and 10x10 m). The wood bulk density and fiber dimensions did not differ in relation to spacing. In the spacing of greatest amplitude (10x10 m), trees tended to have smaller diameters and greater wood density than those with larger diameters. In the radial profile of apparent density, there was an increase in this parameter from pith to bark for the three spacings.